(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
Problem: The research addresses the inherent gap between complex human goals and the limitations of individual capabilities, positioning administrative organization as a fundamental strategy to streamline collective efforts. The problem manifests in organizational challenges where the absence of structure leads to decreased efficiency and conflicting objectives, necessitating a framework that ensures optimal resource allocation. Methodology: The study adopts a descriptive-analytical approach within a theoretical framework, surveying management literature on organization theories. It meticulously analyzes organizational structures and distinguishes between Formal and Informal Organization, evaluating their combined impact on employee behavior and overall institutional dynamics. Results: The findings underscore that sound administrative organization is the cornerstone of efficiency. The theoretical results confirm the necessity of core governing principles—namely Coordination, Hierarchy of Authority, and Unity of Objective—for achieving Institutional Excellence. Furthermore, the study highlights that while formal structures provide clarity, informal organizations significantly shape performance based on management’s ability to integrate them effectively. Application: This study is applied to "Al-Faw Higher Training Institutes" in the Kingdom of Saudi Arabia (2025-2026). The application aims to evaluate how organizational frameworks impact performance efficiency and the quality of training outputs within the Saudi private sector.